GROUNDS FOR REFUSAL OF EXTRADITION IN INTERNATIONAL LAW: POLITICAL OFFENCES AND THE PRINCIPLE OF NONEXTRADITION OF NATIONALS - Khudayberdiyeva Shohista Akmal qizi. (Scholar Express Journals, 2025)
This article examines the grounds for refusal of extradition with particular emphasis on the political offense exception and the principle of nonextradition of a state’s own citizens. These refusal grounds represent enduring features of extradition law, reflecting fundamental concerns related to state sovereignty, political freedom, and the protective relationship between the individual and the state. The study analyzes the concept and evolution of political crimes in extradition law, including the traditional distinction between pure and relative political offenses, and assesses how modern international law has progressively narrowed the scope of the political offense exception, especially in response to terrorism and serious transnational violence. The article also considers United States extradition practice as a contrasting model that prioritizes treaty obligations over nationality-based protection. It concludes that while political crimes and nationality remain relevant grounds for refusal, contemporary international law increasingly seeks to balance these principles with the imperative of preventing impunity through enhanced judicial cooperation and accountability mechanisms.
Keywords: Extradition; grounds for refusal; political offense exception